The Phenolic Content of Pistacia lentiscus Leaf Extract and Its Antioxidant and Antidiabetic Properties - Hamza Bouakline; Saliha Bouknana; Mohammed Merzouki; Imane Ziani; Allal Challioui; Mohamed Bnouham; Abdesselam Tahani; Ali EL Bachiri (The Scientific World Journal)
The aims of this study were to determine the polyphenolic profile, to estimate the total phenolic and flavonoid contents, and to evaluate the antioxidant and antidiabetic activities of the extract of Pistacia lentiscus leaves, and the hydroacetonic mixture was employed as an alternative for common solvents in the extraction process. In order to explain the antidiabetic activity, molecular docking has been performed on the main constituents of the leaf extract. The characterization of the extract has been performed by high-performance liquid chromatography (HPLC) leading to the detection of 20 compounds of which gallic acid, ellagic acid, catechin, kaempferol, and quercetin 3-glucoside were identified using authentic standards. The total phenolic and flavonoid contents, assessed using the Folin–Ciocalteu and quercetin methods, were 394.5 ± 0.08 mg gallic acid equivalent/g dry extract (mg GAE/g DE) and 101.2 ± 0.095 mg quercetin equivalent/g dry extract (mg QE/g DE), respectively. On the other hand, the antioxidant activity of leaf extract, quantified by determining the ability to neutralize the free radical DPPH and β-carotene/linoleate model system, reached the values of 0.0027 ± 0.002 mg/mL and 0.128 ± 0.04 mg/mL, respectively. Regarding the antidiabetic activity, based on the inhibition of pancreatic α-amylase activity, a significant inhibition of about 68.20% with an IC50 value of 0.266 mg/mL had been observed. This finding is consistent with the molecular docking study of the main phenolic compounds of the extracts, where a remarkable binding affinity against α-amylase was observed, with values of −7.631 (kcal/mol), −6.818 (kcal/mol), and −5.517 (kcal/mol) for the major compounds catechin, quercetin-3-glucoside, and gallic acid, respectively.